Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

5+3x-2andx+2(x+1)+1=

Sagot :

Step-by-step explanation:

5 - 3x - 2 = x + 2(x + 1)

Group like terms at the LHS and open the brackets at the RHS.

5 - 2 - 3x = x + 2x + 2

3 - 3x = 3x + 2

Group like terms and make x the subject.

3 - 2 = 3x + 3x

1 = 6x

x = 1/6

Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.